An institutional perspective for evaluating digital transformation in higher education. Insights from the chilean case - Núñez Valdés, Karen Patricia.; Quirós y Alpera, Susana.; Cerdá Suárez, Luis Manuel. (MDPI, 2021)
From a managerial perspective, the rapid diffusion of actions and strategies accelerating the digital transformation of institutions is critical for success. However, in education, business, and management studies, digital transformation can be understood as simple evolutionary processes that enable business models, operational processes, and experiences to be made quickly and efficiently by institutions and agents. This aspect can sometimes lead to opposition, especially when little information is available or in situations of high uncertainty. This research aims to evaluate the involvement of an institutional ecosystem in the digital transformation at universities. Using data collected in Chile, this paper analyzes how the adoption of technologies by universities provides a context for understanding digitalization, measured by the IAU World Higher Education Database (UNESCO). The main finding of this paper is that there is a wide and relevant range of impacts of technological change in higher education institutions, particularly in the categories of values and operations. Additionally, this work serves as a repository of knowledge applicable to similar situations considering the specificities of each particular case. The importance to intervene in relation to certain variables at different levels of managerial performance is described and the implications for higher education institutions are discussed in these pages.
Keywords: Digital Transformation; Higher Education; Institutionalism; Latin America; Chile